KOMUNIKASI PEMASARAN DALAM MEMPERTAHANKAN MANAJEMEN REPUTASI DI SMA SEDES SAPIENTIAE BEDONO - Nurnawati, Ririt Chakri Muninggar, Maya Sekar Wangi & (Transformasi, 2016)
In this research, the methodology that was used is a method of descriptive qualitative, which aims to explain how of marketing communications that there is to retain a management reputations in Sedes Sapientiae Bedono high school. The results of the interviews show that marketing communications made by High School Sedes Sapientiae Bedono, among others through the print media in the form of brochures, famlet, posters, banners, banners and online media (facebooka and website). High School Sedes Sapientiae as a source of near by Bedono has shown interesting way so that prospective students who sign up are not only coming from the area of semarang and surrounding areas, but also come from outside the region who are in Indonesia. For the types of communication strategies used, High School Sedes Sapientiae Bedono choosing and using mediaadvertising and sales promotion, namely promoting by means of presentation to Junior High School‟s builds cooperation before. Then to the transmission or delivery of the message process completed by the High School Sedes Sapientiae Bedono is by way of promoting directly through mediapromotion that have been chosen and effective in the delivery of information. Communication strategies for marketing in decoding, prospective students have a good response. Through a varietyof media promotion that have been selected. It makes an action from its prospective students who decide to enrol into a high school student Sedes Sapientiae Bedono. Reputation management who have obtained High School Sedes Sapientiae Bedono throgh the 4 charge indicators will be to reliable credibility, Image, reability and social responsibility of obtaining good results to maintain the reputation of the school.Keywords: marketing communications, reputation management and maintain